Family Functioning dan Self Control: Pengaruhnya terhadap Academic Procrastination Mahasiswa - Purwono, Clarissa Debora Rhein Love; Wibowo, Moersito Wimbo (Universitas Muhammadiyah Metro, 2025)
This study aims to analyze the influence of family functioning and self-control on procrastination behavior among students. The research subjects consist of 300 active students in Malang City. The method used is a quantitative approach with data collection techniques through three measurement scales: the family functioning scale, the self-control scale, and the procrastination scale. The sampling technique was conducted using purposive sampling. Data analysis was performed using SPSS 20.0 software for Windows with multiple linear regression analysis techniques. The results of the study indicate a highly significant influence of family functioning and self-control on students' procrastination levels. The correlation coefficient of these two variables on procrastination produced a significance value (p) of 0.00 (p < 0.01). The effective contribution of family functioning and self-control to procrastination behavior was 58%. Therefore, this study concludes that family functioning and self-control have a positive and highly significant influence on students' tendency to delay tasks in Malang City.